Challenges in Molecular and Morphological Identification of Sponge Species in Raja Ampat - Aisyah, Siti Zanuba; Zamani, Neviaty Putri; Cahyani, Ni Kadek Dita; Elfahmi, Elfahmi; Syafrizayanti, Syafrizayanti; Arafat, Dondy; Bashari, Muhammad Hasan; Hanif, Novriyandi; Sani, Lalu M. Iqbal; Ayu, Inna Puspa; Akbar, Nebuchadnezzar; Subhan, Beginer; Andriani, Yosie (Marine Science Department Diponegoro University, 2025)
Sponges (Phylum Porifera) are a group of highly diverse, sessile, and filter-feeding basal metazoans, except spongillids. The majority of sponges are marine species that play an important role in benthic habitat by maintaining the stability of marine ecosystems through nutrient cycling, habitat provision, and bioerosion. However, marine sponges are not easily identifiable because of their lack of species-level distinctive morphological features, which limits efforts to monitor actual species biodiversity. Indonesia is home to approximately 850 identified species of marine sponges, and Raja Ampat archipelago of West Papua province is known for its exceptional marine biodiversity. Despite the species abundance, the exact number of sponges in the region is not well-documented due to the lack of specific studies providing comprehensive data on their diversity. Therefore, this study aimed to conduct a DNA barcoding analysis using the mitochondrial cytochrome oxidase I (COI) gene as a marker, combined with morphological analyses of 22 individuals collected in the waters of Waigeo, Mansuar, and Gam Islands in Raja Ampat. The results showed that 3 samples were identified at the species level (Halichondria sp. and Stylissa carteri) with good query cover and percent identity. This showed the possible presence of undescribed or cryptic species, suggesting a severe lack of reference data for both morphology and molecular analyses of marine sponges in the region. Consequently, the analysis showed the presence of a significant gap in the understanding of sponge biodiversity in Raja Ampat's waters.